EVALUATION OF THE ROLE OF INNOVATION IN THE DIVERSIFICATION OF GROSS DOMESTIC PRODUCT IN UZBEKISTAN - Kuziyeva Gulnoza Rashidovna (Labor economics and human capital, 2024)
This article is dedicated to evaluating the role of innovations in the diversification of Gross Domestic Product (GDP) in Uzbekistan. The article scientifically analyzes the importance of innovative activities in ensuring economic growth and inter-sectoral balance. During the research, statistical and economic models were applied to identify the relationship between the degree of diversification and innovation indicators. At the end of the article, strategic directions for supporting innovative activities are proposed. In particular, recommendations are provided on improving mechanisms for promoting innovations by the government, strengthening collaboration between science and industry, and utilizing international experience.